NEW APPROACH TO THE SYNTHESIS OF 3-SUBSTITUTED QUINAZOLIN-4-ONES ON THE ANTRANILIC ACID ETHER BASE (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
A new simple and handy method for obtaining variable 3-substituted quinazolin-4-ones has been developed. The interaction of anthranilic acid methyl ester with dimethylformamide dimethylacetal forms the corresponding new 2-dimethylaminomethyleneamino derivative. Above mentioned derivative was condensed with several primary amines and the targeted 3-substituted quinazolin-4-ones were obtained in good yields.
Keywords: 3-substituted quinazolin-4-ones; new 2-dimethylaminomethyleneamino derivative